Secondary school student Responses to learning the Japanese language at a distance in New Zealand - Setsuo Otsuka; Ken Stevens (Flexible Learning Association of New Zealand, 2012)
This paper describes both the positive and negative aspects of learning the Japanese language at a distance as experienced by secondary school students. Among the former students identified flexibility and teacher' objectivity', and among the latter the lack of face-to-face interaction with both teachers and peers. Based on these responses the authors offer some recommendations and discuss the policy implications.